Conquête ottomane de l'Égypte (1517) : arrière-plan, impact, échos - Lellouch, Benjamin.; Michel, Nicolas. (Middle East and Islamic Studies E-Books Online, Collection 2013, ISBN: 9789004248731., 2013)
Conquête ottomane de l'Égypte (1517) est le premier ouvrage collectif consacré à la victoire de Selīm Ier sur les Mamelouks, qui a fait du sultanat ottoman l'unique puissance musulmane en Méditerranée orientale, et ravalé l'Égypte au rang de province. Il en renouvelle l'approche en faisant appel à des sources ottomanes, arabes et occidentales très variées. Les contributions réunies par Benjamin Lellouch et Nicolas Michel s'attachent à mesurer les transformations structurelles qu'a induites l'événement dans la société, les pouvoirs, la culture littéraire, artistique et matérielle en Égypte. Elles explorent ses antécédents et son impact géopolitique, et restituent les échos, bruyants puis assourdis, qu'il a suscités, au Proche-Orient, en Italie, et plus généralement en Méditerranée. Conquête ottomane de l'Égypte (1517) is the first collective work that deals with Selīm Ist's crushing victory over the Mamluks, which made the Ottoman sultanate into the sole remaining Muslim power in the eastern Mediterranean, and reduced Egypt to the rank of a province. The book offers new insights into this major event by using a wide range of Ottoman and Arabic as well as Western sources. These essays in French and English collected by Benjamin Lellouch and Nicolas Michel examine to what extent the Ottoman conquest altered the structures of Egyptian society, power relations, literature, arts and material culture. They explore both its backgrounds and geopolitical aftermath, and reconstruct its echoes - loud at first, then gradually fading out - in the Middle East, Italy, and the Mediterranean.